pengaruh profesionalisme auditor pada keberhasilan auditor dalam menemukan kecurangan - Ayu Ambalika, I Gusti Agung; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Akuntansi, 2018)
Auditor professionalism is important on the auditor work field. Auditor’s knowledge and skills would be very helpful to identify, judge, and evaluate any audit evidence in order to have a good quality audit evidence.This research was conducted at 7 Public Accounting Firm that existed in Bali by using questionnaire technique as a method of collecting data. The number of samples used in this study were 38 respondents. The analysis technique used is regression analysis test. Based on the results of research conducted, it is known that auditor professionalism has a significant effect on its success in finding fraud in financial statements in an organization. This can show that, the more professional an auditor the auditor's success in finding the cheating will be better. Key Word : Auditor Profesionalism, Finding Fraud